AB1028 Description of a Series of Patients with Childhood Rheumatologic Diseases Assessed in a Transition Unit of an Adult Center. (9th June 2015) - Torrente-Segarra, V.; Juanola Roura, X.; Antόn Lόpez, J.J.; Nolla-Solé, J.M.
Abstract : Objectives: To define the clinical characteristics of patients with childhood Rheumatic diseases who reached a Transition Unit of an Adult Rheumatology Center. Methods: We reviewed the clinical variables in a series of patients seen in the Service Transition Unit of Rheumatology of a tertiary hospital between January 2013 and December 2014. Patients come from a unit of Pediatric Rheumatology where they are transferred to 18 to that Transition Unit. Patients are evaluated per protocol in a monographic specific agenda at the Rheumatology Department in an adult center. They are assisted in adapting at the characteristics of the new hospital. Patients are seen by the Transition Unit for 2 years and then controlled as usual successive visits Rheumatology Department. Both the pediatric center and initially in the adult center, patients are assessed by a specialist Rheumatology Pediatric Rheumatologist. The variables included in this study are: age, diagnosis, presence of clinical activity at the time of the transfer, antirheumatic use of disease-modifying drugs (DMARDs) and use of biological therapy. Results: We have attended a total of 45 patients during the period described. All were 18 years old at the time of transfer. The diagnoses of patients were: Juvenile Idiopathic Arthritis (JIA) oligoarticular-10 cases (22.2%), JIA associated with enthesitis 7 cases (15.5%), Lupus Erythematosus 4 patients (8.8%), Sd autoinflammatory 3 patients, polyarticular JIA, extended oligoarticular JIA, Juvenile Dermatomyositis, Osteoporosis and Morfea 2 cases each and systemic onset JIA, psoriatic JIA, Sd Sjögren, Mixed Connective Tissue disease, Behçet's Disease, Rheumatic Fever and JIA undifferentiated 1 case each. At the time of the transfer, 22 patients (48.8%) were treated with DMARDs (methotrexate, leflunomide, hydroxychloroquine, azathioprine) and 14 patients (31.1%) were on biological therapy (7 adalimumab, etanercept June 1 tocilizumab). A total of 8 patients (17.7%) had clinical activity at the time of the change from pediatric to adult hospital. Conclusions: Transition Unit has enabled us to control a large group of patients with Rheumatic diseases that start in childhood, with a wide range of entities. The complexity of many treatments and disease activity at the time of transfer showed the usefulness of said units in specialized centers. Disclosure of Interest: None declared